SPE Improved Oil Recovery Conference 2016
DOI: 10.2118/179655-ms
|View full text |Cite
|
Sign up to set email alerts
|

Use of Partitioning Tracers to Estimate Oil Saturation Distribution in Heterogeneous Reservoirs

Abstract: Partitioning interwell tracer tests (PITTs) have been used to estimate remaining oil saturations during waterflooding. Compared to core tests, well logs and single well tracer tests, PITTs sample a much larger representative elemental volume (REV) and provide interwell estimates of remaining oil saturation. The test has historically been used to estimate residual oil saturation (Sorw) after waterflooding between injector-producer pairs when the oil is essentially immobile. During polymer flooding, especially w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Thus, the use of a new compound as partitioning tracer in the oilfield must be preceded by an evaluation of its capacity to resist the conditions encountered there. The potential benefits of using PITT as a characterization tool for efficient reservoir management are widely discussed in the literature Dean et al, 2016;Sanni et al, 2018; and such tests https://doi.org/10.1016/j.petrol.2019.106269 Received 6 September 2018; Received in revised form 14 June 2019; Accepted 12 July 2019 can be fundamental for the industry in the future. Increasing the number of compounds tested and thoroughly qualified for use as partitioning tracers in the oilfield will contribute to overcome one of the main current obstacles to the dissemination of this technology.…”
Section: Partitioning Inter-well Tracer Testsmentioning
confidence: 99%
“…Thus, the use of a new compound as partitioning tracer in the oilfield must be preceded by an evaluation of its capacity to resist the conditions encountered there. The potential benefits of using PITT as a characterization tool for efficient reservoir management are widely discussed in the literature Dean et al, 2016;Sanni et al, 2018; and such tests https://doi.org/10.1016/j.petrol.2019.106269 Received 6 September 2018; Received in revised form 14 June 2019; Accepted 12 July 2019 can be fundamental for the industry in the future. Increasing the number of compounds tested and thoroughly qualified for use as partitioning tracers in the oilfield will contribute to overcome one of the main current obstacles to the dissemination of this technology.…”
Section: Partitioning Inter-well Tracer Testsmentioning
confidence: 99%
“…A large number of laboratory experiments and field-scale tests have been conducted to detect NAPL contaminations since the 1990s. The most commonly applied volume sensitive tracers are alcohols of varying chain length, such as 1-hexanol [57][58][59][60] [6,71] and fluorotelomer alcohols [72]. Additionally, sulfur hexafluoride (SF 6 ) [73][74][75][76][77] , perfluorocarbons [61,78], radon-222 [79][80][81], and fluorescent dyes (e.g., rhodamine WT, sulforhodamine B, and eosin) [82] have also been suggested for use as volume sensitive tracers.…”
Section: Volume Sensitive Tracersmentioning
confidence: 99%
“…Tracers are typically employed in industrial (Dean et al., 2016; Huseby et al., 2015; Shen et al., 2017) and environmental (Solcova et al., 2022) settings to characterize attributes of subsurface systems (i.e., reservoirs/aquifer) such as, for example, permeability, porosity, or parameters driving geochemical interactions at a scale of interest. These are chemical compounds that can be added to the fluids residing in the porous formation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, partitioning tracer tests are often performed for the estimation of the residual oil saturation and volume to support enhanced oil recovery operations, eventually through unconventional approaches to increase energy production. Studies related to this technique can be found at the laboratory and field scales (see, e.g., Annable et al., 1998; Dean et al., 2016; Dwarakanath et al., 1999; Huseby et al., 2015; Jin et al., 1995, 1997, Shen et al., 2017). Laboratory scale studies are particularly critical to increase our knowledge of the underlying mechanisms.…”
Section: Introductionmentioning
confidence: 99%